2018
DOI: 10.1089/ast.2017.1716
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Kerogen as a Biosignature Using Colocated UV Time-Gated Raman and Fluorescence Spectroscopy

Abstract: The Mars 2020 mission will analyze samples in situ and identify any that could have preserved biosignatures in ancient habitable environments for later return to Earth. Highest priority targeted samples include aqueously formed sedimentary lithologies. On Earth, such lithologies can contain fossil biosignatures as aromatic carbon (kerogen). In this study, we analyzed nonextracted kerogen in a diverse suite of natural, complex samples using colocated UV excitation (266 nm) time-gated (UV-TG) Raman and laser-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 87 publications
(146 reference statements)
1
15
0
Order By: Relevance
“…In situ techniques, including Raman spectroscopy, have been demonstrated to enable detection of organic material in ice without melting the sample (Rohde et al, 2008;Böttger et al, 2017). Deep-UV (DUV) techniques have also been demonstrated to distinguish microbes and other organic compounds based on their fluorescence spectra (Bhartia et al, 2010;Eshelman et al, 2015;Eshelman et al, 2018;Shkolyar et al, 2018), and field DUV fluorescence instruments have been deployed to study deep marine biospheres, successfully detecting microbe-like signatures (Bhartia et al, 2010;Salas et al, 2015). The work described here builds on prior field instrumentation using DUV fluorescence to study bacteria in situ (Salas et al, 2015) and in icy environments (Rohde et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In situ techniques, including Raman spectroscopy, have been demonstrated to enable detection of organic material in ice without melting the sample (Rohde et al, 2008;Böttger et al, 2017). Deep-UV (DUV) techniques have also been demonstrated to distinguish microbes and other organic compounds based on their fluorescence spectra (Bhartia et al, 2010;Eshelman et al, 2015;Eshelman et al, 2018;Shkolyar et al, 2018), and field DUV fluorescence instruments have been deployed to study deep marine biospheres, successfully detecting microbe-like signatures (Bhartia et al, 2010;Salas et al, 2015). The work described here builds on prior field instrumentation using DUV fluorescence to study bacteria in situ (Salas et al, 2015) and in icy environments (Rohde et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The optical activity from organic and inorganic compounds has also been proposed as a tool for the detection and characterization of biosignatures. For example, kerogen (Marshall et al, 2017; Shkolyar et al, 2018), proteins (Dartnell and Patel, 2014; Lin et al, 2015) and minerals can be associated with the past presence of life in an environment. Gaft et al (2015) showed several minerals in which the optical activity may be associated with rocks formed in different contexts.…”
Section: Investigating the Structure Optical And Magnetic Propertiesmentioning
confidence: 99%
“…Regarding excitation, the kerogen sample in our study has a surface area of ~0.2 cm 2 , which with an LED power of 500 mW results in a fluence of 2.5 W.cm -2 . This value is considerably lower than that provided by a pulsed laser (2.3 105 W.cm -2 , Shkolyar et al 2018), suggesting pulsed laser excitation should be considered for future UV luminescence instruments.…”
Section: Photoluminescence Of Complex Carbonaceous Mattermentioning
confidence: 71%